Legal System for Appeal Against the Judicial Decision Issued for Cessation of Administrative Decision Implementation Case Study (France, Egypt And Jordan) - Almajali, Mohmmad Husien; Alshawabkeh, Faisal Abed Alhafaz (International Journal of Psychosocial Rehabilitation, 2020)
In this research entitled " Legal System for Appeal Against the Judicial Decision Issued for cessation of Administrative Decision Implementation" we addressed in details ways of appeal that are legally approved in the French, Egyptian and Jordanian legal systems for appeal against the first instance administrative courts’ judgments issued for applications of appeal against administrative decision implementation , then conditions of accepting appeal at second instance supreme courts were addressed and finally there was an investigation for implications of accepting appeal against implementation cessation judgments and how administrative supreme courts’ control in Egypt, Jordan and the French state council for the first instance courts decisions issued for cessation the administrative decision implementation.